ISLAMIC MICROFINANCE: AN ADOPTION OF EQUITY FINANCING MODEL IN MALAYSIA - MOHD ABD KHAR, SITI HAJAR (2020)
Microfinance is one among the crucial finance sectors in Malaysia. The micro, small and medium businesses rely on microfinance for finance support.